Hubungan antara Usia Balita, Pemberian Susu Formula, dan Tempat Tinggal dengan Kejadian Diare: Sebuah Studi Analisis Data DHS: The Relationship Between the Age of Toddlers, the Provision of Formula Milk, and Residence Location with the Occurrence of Diarrhoea: An Analysis of DHS Data - Dzulkifli, Achmad; Sumarmi, Sri; Isaura, Emyr Reisha; Syahdana, Achidah Nur; Mahmudiono, Trias; Mahmudah, Mahmudah; Melaniani, RR Soenarnatalina (Universitas Airlangga, 2024)
Background: Approximately 16% of mortality in children under five years old is associated with diarrhoea. In Ghana, diarrhoea is the third most common cause of death among infants. Ghana is one of the countries in Africa with an estimated 1,700 deaths due to diarrhoea in infants. Objectives: This study aimed to determine the relationship between toddlers' age, formula milk consumption, residence location, and diarrhoea occurrence. Methods: This study was a cross-sectional, analytical, observational study. The data was obtained from the Ghana Demographic and Health Survey (DHS) database in 2019. The total number of respondents in the Ghana Demographic and Health Survey (DHS) was 8,362 individuals. Meanwhile, the total number of respondents who meet the inclusion criteria is 2,263 toddlers. Results: This study demonstrated a significant relationship between the occurrence of diarrhoea in toddlers and characteristics related to the toddler's age (p-value<0.001; OR=0.696; 95% CI=0.579-0.837), formula milk consumption (p-value<0.001; OR=2.056; 95% CI=1.629-2.596), and residence location (p-value<0.001; OR=1.719; 95% CI=1.326-2.245). Conclusions: Based on the results of the study, the incidence of diarrhoea in toddlers was correlated with the age of the toddler, formula feeding, and location of residence. Development of diarrhoea research will be needed in relation to health promotion in preventing diarrhoeal diseases.